Knowledge and Attitudes Regarding Covid-19 Prevention in the Music Community - Andayani, Lia H.; Sandra, Ferry; Soulissa, Abdul G.; Handojo, James (e-GiGi, 2022)
Abstract: The escalation of COVID-19 cases both in morbidity and mortality rates in Daerah Khusus Ibukota (DKI) Jakarta and its surrounding areas (JABODETABEK) continues to occur. Adherence in implementing health protocols depends on the knowledge and attitudes of the individuals. This study aimed to assess the knowledge and attitude regarding Covid-19 prevention in an informal community, namely music community. This study was conducted online with 44 participants obtained through convenience sampling method. Participants filled out the questionnaires covering individual characteristics, general knowledge regarding Covid-19, and attitudes towards protective measures against Covid-19. The Mann-Whitney test was used to analyze the differences in the mean score of knowledge based on selected variables. There were 52.4% of participants that had low level of knowledge. Meanwhile, 86.4% of participants had positive attitude towards protective measures against Covid-19. Significant differences were found in the mean scores of knowledge based on age (p=0.001), place of residence (p=0.004), and occupational status (p=0.032). In conclusion, most participants of the music community in Jakarta and surrounding areas have low level of knowledge, however, they have positive attitude towards protective measures against Covid-19.Keywords: Covid-19; knowledge; attitude; music communityÂ Abstrak: Peningkatan kasus Covid-19 baik dalam angka morbiditas maupun mortalitas di wilayah Daerah Khusus Ibukota (DKI) Jakarta dan sekitarnya (JABODETABEK) masih berlangsung. Kepatuhan dalam menerapkan protokol kesehatan bergantung pada pengetahuan dan sikap individu. Penelitian ini bertujuan untuk mengetahui gambaran pengetahuan dan sikap mengenai pencegahan Covid-19 pada salah satu komunitas informal di masyarakat, yaitu komunitas musik. Penelitian ini dilakukan secara daring dengan 44 peserta yang didapatkan melalui metode convenience sampling. Peserta mengisi kuesioner survei yang berisi data karateristik individu, pengetahuan umum, dan sikap terkait Covid-19. Uji Mann-Whitney digunakan untuk melihat perbedaan rerata nilai pengetahuan berdasarkan setiap variabel. Hasil penelitian mendapatkan sebanyak 52,4% responden memiliki tingkat pengetahuan rendah namun 86,4% responden memiliki sikap positif terhadap upaya pencegahan penularan Covid-19. Perbedaan rerata nilai pengetahuan secara bermakna ditemukan berdasarkan usia (p=0,001), wilayah tinggal (p=0,004), dan status pekerjaan (p=0,032). Simpulan penelitian ini ialah sebagian besar komunitas musik di DKI Jakarta dan sekitarnya memiliki tingkat pengetahuan rendah namun memiliki sikap positif terhadap upaya pencegahan penularan Covid -19.Â Kata kunci: Covid-19; pengetahuan; sikap; komunitas musik